On the periodic problem of control for infinite differential systems with pulse effect - Teplinsky, Yu.V.; Luchik, V.E. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Samoilenko's numerical-analytic method is modified for differential systems with pulse action in a space of bounded sequences. In certain cases of linear systems of equations, this method makes it possible to solve the periodic control problem with a predetermined accuracy.